Comparative Study for the Determination of Gemifloxacin by HPLC and Microbiological Methods from Pharmaceutical Preparations and Biological Samples - Eylul Kiymaci, Merve; Gumustas, Aysen; Gumustas, Mehmet; Akin, Ahmet; Aysil Ozkan, Sibel (Current Pharmaceutical Analysis, 2015)
The fluoroquinolones have broad-spectrum activity, good absorption in gastrointestinal canals and superior tissue penetration. Because of these properties, they have been used to treat a wide range of infections. In this study high performance, liquid chromatography and microbiological methods have been developed for the determination of Gemifloxacin (GEM) in pharmaceutical preparations and human plasma. Microbiological assay was performed using Kirby Bauer disk diffusion method according to Clinical and Laboratory Standards Institute criteria, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 29213 were used as test microorganisms. Different concentrations of GEM were absorbed into antimicrobial susceptibility blank disks. Mueller Hinton Agar plates were inoculated with each microorganism that was adjusted to the turbidity of Mc Farland 0.5 standard separately and dried antibiotic disks were placed on the surface of agar. Plates were incubated and inhibition zone diameters were measured. The chromatographic separation was performed using Waters X-Bridge RP-18 column with an isocratic mode. The separation was carried out at 25 °C. All necessary validation parameters and system suitability test results were obtained. Also, interday and intraday studies were realized. RSD % values were reported to show the precision of the method. The proposed and validated methods were applied for the analysis of GEM in pharmaceutical formulations and human plasma for both methods.
Keywords: pharmaceuticals